Answer:
I believe the answer is x = - 11. The equation would be 4(N + 3) = 2N - 10.
Step-by-step explanation:
To solve the equation, first multiply everything in the parenthesis by 4.
N x 4 = 4N
3 x 4 = 12
The new equation is 4N + 12 = 2N - 10.
Next, move the 12 to the right side of the equation by subtracting it from both sides.
4N + 12 = 2N - 10
- 12 - 12
4N = 2N - 22
Then, move the 2N to the left side of the equation by subtracting it from both sides.
4N = 2N - 22
-2N -2N
2N = -22
(In the second 2 steps, you are combining like terms.)
Finally, divide both sides by 2 to get what N equals.
2N/2 = N
-22/2 = -11
The final answer is N = -11.